Bet hedging via multiple mating: A meta-analysis. (1st January 2016) - Holman, Luke
Abstract: Polyandry has been hypothesized to allow females to "bet hedge" against mating only with unsuitable mates, reducing variance in offspring fitness between members of a polyandrous lineage relative to a single-mating one. Theoretically, this reduction in fitness variance could select for polyandrous genotypes even when polyandry carries a direct cost, especially in small populations. However, this hypothesis is controversial and difficult to test empirically. Here, I apply a novel simulation model to 49 published empirical datasets, and quantify the potential selective advantage of multiple mating via reduced offspring fitness variance. For a wide range of assumptions, including those that most favor the evolution of bet hedging, I show that any fitness gains are meager. The variance in offspring quality caused by mate identity does not appear to be high enough for bet hedging to drive the evolution of polyandry.